Diagnosis for Latent Tuberculosis Infection: New Alternatives - Carranza, Claudia; Pedraza-Sanchez, Sigifredo; de Oyarzabal-Mendez, Eleane; Torres, Martha (Frontiers in Immunology, 2020)
Latent tuberculosis infection (LTBI) is a subclinical Mycobacterial infection defined on the basis of cellular immune response to mycobacterial antigens. The tuberculin skin test (TST) and Interferon gamma release assay (IGRA) are used to establish the diagnosis of LTB. However, neither TST, nor IGRA are useful to discriminate between active and latent tuberculosis. Moreover, these tests cannot be used to predict whether an individual with LTBI will develop active tuberculosis (TB) or whether therapy for LTB could be effective to decrease the risk to develop active TB. Therefore, there have been some efforts to identify an immunological marker that could be useful in distinguishing LTB from TB and in evaluating the effectiveness of treatment of LTB on the risk for progression to active TB. These efforts have included strategies focused on the components of host immunity involved in the response to latency associated mycobacterial antigens and transcriptional analysis in LTBI individuals.